WOMEN BODY AND ITS FUNCTIONS IN DYSTOPIAN LITERATURE: SEXUAL COMMODITY, SEXUAL PLEASURE, AND REPRODUCTIVE NATURE - Avi Ainul Fikri; Ida Rosida (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This research aims to show how women’s bodies and their functions shape the role of women in dystopian society reflected in Blade Runner 2049. Cyborgfeminism theory by Donna Haraway and postgenderism theory by James Hughes and George Dvorsky with a qualitative method are used to analyze the corpus. The results show that the role of women in the dystopian society functions as a human’s reproduction while women’s body is viewed as sexual commodities and valued for its sexual pleasure. In conclusion, this research can be used as a foreshadowing of how women and their roles will be in a dystopian society where the near-future capabilities of Artificial Intelligence and robotics may provide men as the superior gender which can dominate over the bodies and existence of women.